Bio-Energy with CCS (BECCS) performance evaluation: Efficiency enhancement and emissions reduction. (1st June 2017) - Bui, Mai; Fajardy, Mathilde; Mac Dowell, Niall
Highlights: A study of biomass co-firing with CCS is presented. The impact on process efficiency of a range of solvents is considered. We show that with heat recovery, carbon negative power plants can be 38% efficient. BECCS plant efficiency and carbon negativity are strongly related. Abstract: In this study we evaluate the feasibility of the recovery of waste heat from the power plant boiler system of a pulverised fuel power plant with amine-based CO2 capture. This recovered heat can, as a function of fuel type and solvent selection, provide up to 100% of the heat required for solvent regeneration, thus obviating the need for withdrawing steam from the power plant steam cycle and significantly reducing the efficiency penalty imposed upon the power plant by the CO2 capture process. In studying the thermochemistry of the combustion process, it was observed that co-firing with low moisture biomass achieved higher adiabatic flame temperatures (AFT) than coal alone. The formation and emission of SO X reduced as biomass co-firing proportion increased, whereas NO X emissions were observed to be a function of AFT. The power generation efficiency of a 500 MW 50% co-firing BECCS system increased from 31%HHV with a conventional MEA solvent, to 34%HHV with a high performance capture solvent. The heat recovery approach described in this paper enabled a further efficiency increase up to 38%HHV with the high performant solvent. Such a system was found to remove 0.83 Mt CO 2 from the atmosphere per year at 90% capacity factor.